Adverse Effects of Andrographolide Derivative Medications Compared to the Safe use of Herbal Preparations of Andrographis paniculata: Results of a Systematic Review and Meta-Analysis of Clinical Studies - Shang, Ya-xi; Shen, Chen; Stub, Trine; Zhu, Si-jia; Qiao, Shu-yu; Li, Yu-qi; Wang, Rui-ting; Li, Jing; Liu, Jian-ping (Frontiers in Pharmacology, 2022)
Background and objective Andrographis paniculata (AP) is a traditionally used herbaceous plant, whose main active constituent is andrographolide. Andrographolide derivative medications and herbal preparations of AP are often used to treat respiratory tract infections. This study aims to systematically evaluate the safety of andrographolide derivative medications and herbal preparations of AP based on clinical studies. Methods English and Chinese databases were searched for all types of clinical studies that reported adverse drug reactions (ADRs) and adverse events (AEs) of andrographolide derivative medications and herbal preparations of AP. The ADRs and AEs were classified according to manifestations, and graded according to severity. Single-rate meta-analysis was performed for ADR incidence using R software. Results A total of 262 studies were included, including 125 randomized controlled trials, 23 non-randomized controlled trials, 6 case series, and 108 case reports. In 9490 participants using andrographolide derivative injections, 383 (4.04%) reported ADRs. Meta-analysis showed that the ADR incidence of three most frequently used injections of andrographolide derivatives (andrographolide sulfonate, potassium sodium dehydroandrographolide succinate, and potassium dehydroandrographolide succinate) were 5.48% (95% CI [4.47%, 6.72%]), 3.69% (95% CI [2.59%, 4.94%]) and 5.33% (95% CI [3.68%, 7.72%]), respectively, which may be slightly higher than the actual ADR incidence, because only studies that reported the occurrence of ADRs or AEs were included, but studies without ADR and AE were not included. The ADRs of andrographolide derivative injections were mainly gastrointestinal, skin and subcutaneous tissue disorders, and anaphylaxis. Fifty-five patients experienced life-threatening anaphylactic shock, three patients died, and the causation attributed to the andrographolide derivative injection. Other ADRs were mild, moderate or medically significant. Nine herbal preparations of AP were tested in 10 studies, and the reported ADRs were mainly mild to moderate gastrointestinal, skin and subcutaneous tissue disorders. Except for five patients using andrographolide derivative injections eventually died, most of the ADRs were alleviated after drug withdrawal and symptomatic treatment. Conclusions The ADRs of andrographolide derivative medications are few, but can be life-threatening, mainly gastrointestinal, skin and subcutaneous tissue disorders, and anaphylaxis. Injections of andrographolide derivatives should be used with caution. Herbal preparations of AP are essentially safe.